Revisión especial al área administrativa y su incidencia en la rentabilidad de la compañía de transporte pesado Interzulema S.A., cantón Buena Fe, año 2013 - Sánchez Morales, Lady Alexandra (2015)
The terrestrial transport in the Ecuador is considered as a strategic sector for the National Government, this is due to that people's thousands and companies have to make use of this means of transport to mobilize their products of a place to other, as he/she makes it the Company INTERZULEMA CORP. located in the Canton Good Faith, road to Sacred Domingo to 300 meters of the former Commission of Traffic, but it was identified that many administrative processes are not completed as the training to their employees, the elaboration of strategic plans, among other inconveniences that affect the development of the same one, is for this reason that our objective is to carry out a Special Revision to the Administrative Area. Methodologically this investigation is of descriptive character, using the field investigation, the same one that allowed to analyze in a critical way the theoretical and practical foundations of the investigation that you/they helped to the execution of this work. Likewise it was acquired knowledge of the audit marks, the work papers and the discoveries. Summarizing the results of the Execution of this investigation obtained under a level of trust of 69% what is considered moderate and with a level of risk of 31% being in the moderate range, also the administrative process that was analyzed that will serve to improve the execution of the laws, political and regulations those that helped to correct the functions and administrative processes that impact in the profitability. It is necessary to emphasize that the important of this project is to analyze to the Administrative area and that by means of the report he/she helps the directive to make appropriate decisions for the future of the Company.